PROBLEM HASRAT BELAJAR MAHASISWA DAN TAWARAN KONTEKSTUALISASI KONSEP RUANG PUBLIK JURGEN HABERMAS DI IAIDA SEBAGAI SOLUSINYA - Ginanjar Prastyanto (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract This research departs from our anxiety as IAIDA lecturers when dealing with students in the lecture hall, who seem less eager to learn. This research is not only intended to understand a problem, but also aims to explore a solution to solve it. The perspective we use to examine this problem is Lacan's theory of desire. Meanwhile, to explore solutions that can be used to solve these problems, we use critical theory, especially Habermas's concept of public space, which is based on communication free from domination. The research method we use is qualitative. The scope of our research is IAIDA students who are staying at the Darussalam Islamic Boarding School Blokagung. The data mining method we used was in-depth interviews, and the number of informants was three students. The data analysis method is critical reflection. The results of our study illustrate that students' low desire to learn is because they do not experience a mirror moment when they are in the lecture room. The solution that we offer to solve this problem is that IAIDA needs to build a scientific public sphere with the caretakers of Darussalam Blokagung.